2015
DOI: 10.1167/iovs.15-17664
|View full text |Cite
|
Sign up to set email alerts
|

Visible Versus Near-Infrared Optical Performance of Diffractive Multifocal Intraocular Lenses

Abstract: In addition to changes in add power, the optical performances of the DMIOLs measured under either VIS or NIR illumination are considerably different. Whereas they show two distinct (near and far) foci under VIS light, their optical performances under NIR illumination are clearly biased in favor of their far focus. These results may help prevent a misleading use of NIR-based clinical instruments for the assessment of eyes implanted with DMIOLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Lee et al [ 77 ] also reported a mean OSI of 1.82 with multifocal IOLs. However, the validity of all these studies with MIOLs is questionable because of the known limitations of the near-infrared optical performance of diffractive multifocal intraocular lenses [ 78 ], or the first-pass in the double-pass technique that can be affected by the size of the first ring [ 79 ]. Finally, OSI has found to be correlated with straylight parameters and even related to driving safety [ 43 ].…”
Section: Objective Technologies For Lens Evaluationmentioning
confidence: 99%
“…Lee et al [ 77 ] also reported a mean OSI of 1.82 with multifocal IOLs. However, the validity of all these studies with MIOLs is questionable because of the known limitations of the near-infrared optical performance of diffractive multifocal intraocular lenses [ 78 ], or the first-pass in the double-pass technique that can be affected by the size of the first ring [ 79 ]. Finally, OSI has found to be correlated with straylight parameters and even related to driving safety [ 43 ].…”
Section: Objective Technologies For Lens Evaluationmentioning
confidence: 99%
“…3,4 It assumes a pinhole object at infinity and a charge-coupled device (CCD) camera with linear response for digital image acquisition. The method first applies an edge-detection algorithm to segment the central core of the pinhole image at the focus plane of the lens (either the distance or the near focus in a 2f-IOL) and quantifies the amount of light intensity in the core (I core ) relative to the intensity in the full image that comprises the core and the background (I total ¼ I core þ I background ).…”
Section: Through-focus Energy Efficiency Of a Refractivediffractive Bmentioning
confidence: 99%
“…In addition to LCA, the energy distribution between the distance and near images of diffractive 2f-IOLs also shows a strong dependency on wavelength. 2,3 In this work, we studied and measured the chromatic properties of 4 aspheric diffractive 2f-IOLs (2 nonapodized and 2 apodized of different add power) using an experimental setup arranged on an optical bench. Two monofocal (1f-IOL) counterparts (Tecnis model ZA9003, from Abbott Medical Optics, and AcrySof model SN60WF, from Alcon) of the nonapodized and apodized 2f-IOLs, with similar base power, aspheric design, and material, also have been included as references in our study.…”
mentioning
confidence: 99%
“…11,21 Ravikumar et al 16 showed computationally that achromatization by a diffractive IOL provided significant improvement in polychromatic retinal image quality. Diffractive multifocal IOLs in particular have interesting chromatic properties 12,22 because they are subject to both refractive chromatic aberration and wavelength-dependent diffractive effects. In a recent publication, Millán et al 23 evaluated, theoretically and on-bench, the LCA and through-focus energy efficiency of bifocal IOLs of two different designs and materials.…”
Section: Discussionmentioning
confidence: 99%
“…The dependence of the magnitude of LCA on distance is in agreement with previous studies that accounted for LCA in diffractive multifocal IOLs by optical simulations or on-bench measurements. Vega et al 22 compared the optical performance on-bench of diffractive multifocal IOLs with visible and near-infrared light and studied the variation in the energy balance between the different foci of the IOL, which is related to the dependence of the diffraction efficiency with wavelength. Multifocal IOLs often exhibit an asymmetrical energy distribution, normally biased to benefit the far focus against near/intermediate focus for larger pupils, particularly in apodized designs (eg, the FineVision POD F IOL) and with large pupils.…”
Section: Discussionmentioning
confidence: 99%